Towards a corpus-driven approach to audiovisual translation (AVT) reception: A case study of YouTube viewer comments - Wu, Zhiwei; Chen, Zhuojia (The Journal of Specialised Translation, 2022)
Although reception studies on audiovisual translation (AVT) have embraced new research methods and tools, user-generated comments on video-streaming platforms are yet to be systematically examined by AVT scholars. The main objective of this paper is to establish the plausibility of a corpus-driven approach to audience reception. Using a popular YouTube channel Dianxi Xiaoge as an example case, we built a corpus of viewer comments and conducted collocation and concordance analyses. The findings revealed that (a) viewers posted many more comments requesting subtitles than acknowledging the provision of subtitles; (b) audience responses could be specifically grouped into ten themes (comprehension, integral viewing, linguistic quality, subtitle presentation, marked languages, emotional reactions, prosumption, subtitle-evoked viewership, cultural pursuit, and language acquisition); (c) diachronically, each peak of comments about the presence of non-English subtitles was preceded by two to three peaks of comments about their absence, pointing to possible patterns between audience reception and subtitle production. To illustrate the heuristic values of these corpus findings, we discuss the audience insights vis-à-vis the scholarly interests of AVT researchers. We also discuss the advantages and limitations of a corpus-driven approach to AVT reception.